A new methodology for automated Petri Net generation: Method application. (May 2019) - Latsou, Christina; Dunnett, Sarah J.; Jackson, Lisa M.
Highlights: Full automated PN generation taking as input a topology diagram as used in industry. Direct transformation of a UML AD of a system/process to the corresponding PN. Handling and efficiently modelling systems/processes with dependencies and loops. Providing generic applicability, without targeting specific domains.